Relay protection coordination with generator capability curve, excitation system limiters and power system relay protections settings - Buha, Danilo B (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
The relay protection settings performed in the largest thermal powerplant (TE “Nikola Tesla B“) are reffered and explained in this paper. The first calculation step is related to the coordination of the maximum stator current limiter settings, the overcurrent protection with inverse characteristics settings and the permitted overload of the generator stator B1. In the second calculation step the settings of impedance generator protection are determined, and the methods and criteria according to which the calculations are done are described. Criteria used to provide the protection to fulfil the backup protection role in the event of malfunction of the main protection of the transmission system. are clarified. The calculation of all protection functions (32 functions) of generator B1 were performed in the project "Coordination of relay protection blocks B1 and B2 with the system of excitation and power system protections -TENT B"